2009
DOI: 10.1016/j.ejcts.2009.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Functional single ventricle with extracardiac total anomalous pulmonary venous connection☆

Abstract: The mid-term results of the surgical repair of functional single ventricle with supracardiac or infracardiac TAPVC are acceptable. The surgical treatment of patients with mixed TAPVC and with severe atrioventricular valve regurgitation is not promising, but can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
2
23
2
Order By: Relevance
“…The occurrence of postoperative PVO did not reduce survival, but had a significant negative impact on Fontan completion [16]. Nakata et al [17 ]showed that 26 patients who underwent surgical repair of a functional single ventricle and extracardiac TAPVC had a survival after the repair of TAPVC of 58 and 54% at 1 and 5 years, respectively. However, TAPVC was not found to be an important contributor to mortality in our study and the mortality was very high among patients with anomalous pulmonary venous connections and PVO; 3 out of the 5 patients died.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of postoperative PVO did not reduce survival, but had a significant negative impact on Fontan completion [16]. Nakata et al [17 ]showed that 26 patients who underwent surgical repair of a functional single ventricle and extracardiac TAPVC had a survival after the repair of TAPVC of 58 and 54% at 1 and 5 years, respectively. However, TAPVC was not found to be an important contributor to mortality in our study and the mortality was very high among patients with anomalous pulmonary venous connections and PVO; 3 out of the 5 patients died.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors include patient age at the time of repair, morphologic connection, presence of pulmonary venous obstruction, and associated cardiac defects. Recent reviews have reported the neutralization of these risk factors over the last several decades [3, 4]. The majority of this data has been produced by single center retrospective experiences [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…TAPVC can be associated with a univentricular heart and needs to be addressed at the time of the initial BDG or at the time of the TCPC . An unobstructed cardiac TAPVC with unrestricted mixing of blood at the atrial level is an exception because all the pulmonary venous and systemic venous return mix freely.…”
Section: Discussionmentioning
confidence: 99%
“…TAPVC can be associated with a univentricular heart and needs to be addressed at the time of the initial BDG or at the time of the TCPC. 1 An unobstructed cardiac TAPVC with unrestricted mixing of blood at the atrial level is an exception because all the pulmonary venous and systemic venous return mix freely. In our patient, this was not the case as there was restriction at the mouth of the CS and at the level of the interatrial septum, thus requiring unroofing of the CS and enlargement of the ASD.…”
Section: Discussionmentioning
confidence: 99%